2022
DOI: 10.3346/jkms.2022.37.e87
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Splenomegaly in Patients With Polycythemia Vera

Abstract: Background Non-palpable splenomegaly in patients with polycythemia vera (PV) has seldom been addressed. In this retrospective study, we evaluated non-palpable, volumetric splenomegaly defined based on age- and body surface area (BSA)–matched criteria in patients with PV diagnosed according to the 2016 World Health Organization diagnostic criteria. Methods Patients with PV who underwent abdominal computed tomography (CT) and who had palpable splenomegaly at diagnosis fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 26 A small study in South Korea that enrolled 125 PV patients reported that only 8% had palpable splenomegaly. 27 This study presented records of splenomegaly in 3.0% of low-risk patients and 3.8% in high-risk patients. Although the lack of routine sonography and motivation to record could be the reasons for the low percentage of splenomegaly in Taiwan, possible genetic factors resulting in differential phenotypes remain an intriguing topic for future study.…”
Section: Discussionmentioning
confidence: 83%
“… 26 A small study in South Korea that enrolled 125 PV patients reported that only 8% had palpable splenomegaly. 27 This study presented records of splenomegaly in 3.0% of low-risk patients and 3.8% in high-risk patients. Although the lack of routine sonography and motivation to record could be the reasons for the low percentage of splenomegaly in Taiwan, possible genetic factors resulting in differential phenotypes remain an intriguing topic for future study.…”
Section: Discussionmentioning
confidence: 83%
“…Abdominal CT is not routinely performed during the initial evaluation of ET patients [ 32 ]. The clinical relevance of volumetric splenomegaly and splenic infarction detected using abdominal CT performed at the time of diagnosis of Ph - MPN has been previously evaluated [ 23 , 33 , 34 ]. Furthermore, in a small proportion of patients, abdominal CT has been used to detected asymptomatic malignancies at the time of diagnosis of Ph - MPN.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, abdominal CT detects volumetric splenomegaly in all pre-PMF patients and in only 50% of ET patients at diagnosis [ 7 ]. PV patients with volumetric splenomegaly at diagnosis had a poorer prognosis than those without; however, the prognosis is better than that of patients with palpable splenomegaly [ 8 ]. In addition, abdominal CT performed at the time of MPN diagnosis revealed asymptomatic splenic infarction [ 9 ] and abdominal aortic calcification, indicative of a poor prognosis (submitted for publication).…”
mentioning
confidence: 99%
“…Despite these limitations, we found that a small population of Ph - MPN patients had asymptomatic splanchnic thrombosis and malignant tumors at the time of MPN diagnosis. As mentioned earlier, we previously reported that volumetric splenomegaly and asymptomatic splenic infarction detected by abdominal CT performed at the time of diagnosis are clinically useful for determining the diagnosis and prognosis [ 7 - 9 ]. The advantages of performing abdominal CT may offset the risks associated with radiation exposure and medical costs.…”
mentioning
confidence: 99%